2021
DOI: 10.1002/cpp.2577
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of schema modes

Abstract: A fundamental question in psychotherapy is whether interventions should target client problems (i.e., problem‐focused approaches) or client strengths (i.e., strength‐focused approaches). In this study, we first propose to address this question from a network perspective on schema modes (i.e., healthy or dysfunctional patterns of co‐occurring emotions, cognitions, and behaviours). From this perspective, schema modes mutually influence each other (e.g., healthy modes reduce dysfunctional modes). Recent evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Nine of the 27 studies were conducted by a research group under Professor Atkins, who successfully created an automatic transcription and evaluation tool for short term psychotherapy, namely motivational interviewing ( 21 29 ). Ten of the 27 excluded studies either tried to predict the outcome of cognitive behavior therapy by using natural language processing, or tried to predict optimal therapeutic interventions with sociodemographic data ( 30 40 ). Another 16 studies excluded were reviews about machine learning and its utilization within psychotherapy, psychopharmacotherapy, and diagnostics ( 19 , 27 , 38 , 41 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the 27 studies were conducted by a research group under Professor Atkins, who successfully created an automatic transcription and evaluation tool for short term psychotherapy, namely motivational interviewing ( 21 29 ). Ten of the 27 excluded studies either tried to predict the outcome of cognitive behavior therapy by using natural language processing, or tried to predict optimal therapeutic interventions with sociodemographic data ( 30 40 ). Another 16 studies excluded were reviews about machine learning and its utilization within psychotherapy, psychopharmacotherapy, and diagnostics ( 19 , 27 , 38 , 41 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been empirically shown that although the HA is not central to the network of maladaptive modes, it is still the most important predictor to differentiate people with personality disorder problems from those without a diagnosis of PD ( 30 ). Moreover, it plays an important role in the change process during treatment ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the function of the HA is argued to be central to change in schema therapy ( 16 , 27 , 28 ). Similarly, the importance and centrality of the vulnerable child (VC) mode were established both theoretically ( 21 , 22 ) and empirically ( 28 30 ). The VC contains emotionally painful experiences and distressing emotions, and it can be very painful to stay in contact with the VC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the small sample size, another possible explanation is that individuals with narcissism successfully block the awareness of vulnerable emotions rather than adopt self-soothing behaviours (Bamelis et al, 2011). In fact, recent network analysis on modes (Aalbers, 2021) showed a positive association between lonely child SM and detached self-soother SM in individuals without PDs, but not in individuals with PDs (Aalbers, 2021). They hypothesize that people without a PD are able to adopt self-soothing measures as adequate coping and people with a PD are not.…”
Section: Discussionmentioning
confidence: 99%